Design and application of a pressure relief pad for preventing pressure injuries (一种防压力性损伤减压垫的设计与应用) - ZHANG Yitian (张怡天); SUN Xiumei (孙秀梅); LI Jingwen (李静文) (中西医结合护理)
Prone position ventilation is a kind of ventilation strategy for severe patients, especially patients with acute respiratory distress syndrome. Pressure injury is the most common complication of prone position ventilation, and effective preventive and decompression tools can reduce the occurrence of stress injury during prone position. This study introduces the design and use method of a utility model anti-pressure injury decompression pad, which can change the pressure on the left and right positions of patients in prone position by feeding or releasing water into the water sac on the silicone pad, which can relieve the pressure on vulnerable skins, reduce the occurrence of pressure injury, and reduce the work burden of medical staff. (俯卧位通气是一种针对重症患者, 尤其是急性呼吸窘迫综合征患者的通气策略。压力性损伤是俯卧位通气最常见的并发症, 有效的预防和减压工具能够降低俯卧位期间压力性损伤的发生风险。本研究介绍了一款实用新型防压力性损伤减压垫的设计和使用方法, 其可以通过向硅胶垫上的水囊进行进水或放水的方式, 来改变俯卧状态下患者的左、右体位受到的压力, 对患者的皮肤起到缓解作用, 降低压力性损伤的发生, 同时减轻医护人员的工作负担。)